Effectiveness of Short Message Service (SMS) based Glycaemic Control - Tariq, Maria; Nisar, Shazia; Anwer, Ayesha; Ellahi, Ahtesham; Khan, Muhammad Shahid; Hussain, Muhammad Zahid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To find out the effectiveness of short message service (SMS) on glycaemic control among patients with diabetes at a tertiary care hospital in Rawalpindi. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Endocrinology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan to Jul 2020. Methodology: A total of 218 patients with diabetes were included in the study. Patients were randomized into two groups by lottery method. Group-A received a tailored SMS package daily for six months along with printed dietary instructions, while Group-B was given only printed dietary instructions. After six months, HbA1c levels and other sociodemographic factors were compared among the two Groups A and B. Results: In Group-A (SMS-Group) mean HbA1c levels reduced from 9.3±2.0 to 7.0±0.4 compared to Group-B (non-SMSGroup) with mean HbA1c levels from 9.7±1.8 to 8.8 ±1.4. Before SMS intervention, all variables, including HbA1c levels between the two groups, were insignificant. However, the use of structured SMS-based intervention in Group-A showed a statistically significant reduction in HbA1c levels compared to Group-B (p-value <0.05). The mean difference was 1.77(95% CI:-2.44 to -1.10). Conclusion: This study showed Short Message Service (SMS) effectiveness by significantly reducing glycaemic levels (HbA1c)among people with diabetes compared to conventional methods of diabetic education for glycaemic control.